Implementation of the Village Fund Allocation Policy (ADD) in Sindanghayu Village, Saketi District, Pandeglang Regency in 2021 - Supriatno, Eko; Putri, Irpani Padilah Eka (CV. Lenggogeni Data Publishing, 2023)
This study aims to analyze the implementation of the Village Fund Allocation (ADD) policy in Sindanghayu Village, Saketi District, Pandeglang Regency, in 2021. The research uses a descriptive qualitative approach with interviews, observations, and documentation as data collection techniques. The informants consisted of village officials, members of the Village Consultative Body (BPD), and community beneficiaries. The findings indicate that the implementation of the ADD policy has been relatively effective, supported by strong community participation in village development planning meetings. The village government successfully prioritized the use of funds for basic infrastructure such as road construction and clean water facilities. However, challenges remain, including delayed fund disbursement and limited administrative capacity among village officials. Overall, the ADD policy implementation in Sindanghayu Village reflects the local government’s commitment to improving public welfare through transparent and participatory governance.